The productivity paradox: Policy lessons from MICROPROD - Gregory Claeys; Maria Demertzis (Bruegel, 2021)
Productivity growth in Europe has been on a downward trend for several decades. Given that productivity growth is a crucial source of output growth, particularly in an aging society like the European Union, it is crucial to understand what is driving this slowdown and what the potential consequences are for our economic model and for citizens' welfare.Some explanations for this trend are global in nature, but there are also significant dif-ferences in country structures in Europe that have led to different outcomes and that need to be accounted for before policy prescriptions can be made.The objective of MICROPROD, an EU-wide research project that runs until the end of 2021, is to contribute to this research strand by using data from various European countries to study the microeconomic mechanisms behind this macroeconomic phenomenon. In particular, the aim is to understand the challenges posed to Europe by the fourth industrial revolution and its impact on productivity in the context of globalisation and digitalisation, and to recommend policies to address these challenges.MICROPROD researchers have so far delivered 20 papers on four broad issues relevant for today's policy debates: the measurement and effects of intangible capital on productivity; the impact of globalisation, international trade and the integration of global value chains (GVCs) on productivity; factor allocation and allocative efficiency; and finally the social consequences of the two structural shocks Europe has faced in the last two decades: globalisation and technological progress. This Policy Contribution reviews the main conclusions of these 20 MICROPROD papers and how they inform policy debates. However, the mid-point of the three-year MICROPROD project also coincided with the start of the COVID-19 crisis, which might have accelerated some trends or possibly reversed others. We therefore discuss how some of the messages of MICROPROD research may contribute to our understanding of the current crisis and its aftermath.
Keywords: 330